KELAYAKAN BAHAN AJAR DALAM PEMBELAJARAN TEMATIK DI KELAS V SDN 39 PONTIANAK KOTA - Agung Perkasa; Abdussamad Abdussamad; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the feasibility of thematic learning teaching materials in class V SDN 39 Pontianak City. The research method used is descriptive qualitative. This research was conducted at SDN 39 Pontianak City. Sources of data in this study were teaching materials made by fifth-grade teachers at SDN 39 Pontianak City, as many as three teaching materials on theme 5, sub-theme 3, learning 1, 3, and 5. The method of collecting data in this research used interviews and documentation studies. The results showed that the teaching materials used by teachers in thematic learning in class V at SDN 39 Pontianak City were considered quite feasible. For the feasibility of the content and linguistics of teaching materials in thematic learning, theme 5, sub-theme 3, 1st, 3rd, and 5th lessons used by teachers are considered appropriate and in line with the guidelines according to the BSNP. As for the feasibility of presenting teaching materials in thematic learning of theme 5, sub-theme 3 of the 1st, 3rd, and 5th learning used by teachers, it is considered inappropriate and not in line with the guidelines according to the BSNP.Keywords: Feasibility, Teaching Materials and Thematic Learning